Psychological markers of codependent behavior: theory and practice - Анастасия С. Колёнова; Анна М. Кукуляр; Лидия А. Дятлова (Rossijskij psihologičeskij žurnal., 2023)
Introduction. The purpose of the article is an analytical review of scientific approaches to the study of the features of psychological markers of codependent behavior. Modern approaches to the study of this phenomenon from the point of view of theoretical and practical aspects, reflecting the fragmentary nature of the representation of this concept, are considered. There are not only several definitions of the concept of "codependency", but also many approaches to its study. Based on the theoretical analysis of various approaches, the author's definition of the phenomenon was proposed, which reflects the scientific novelty of the study. The theoretical justification of the problem under study was carried out on the basis of the analysis of literary sources, comparative analysis and generalization of foreign and domestic approaches to the term "codependency" under study, approbation of the author's interpretation of the term under study. Results. Based on the analytical review, psychological markers of codependent behavior are identified, manifested through a learned set of behavioral forms, adaptation disorders, and various personality disorders. It is shown that the description of psychological characteristics related to the phenomenon of codependency is quite extensive, but it is not systemic. The ideas are outlined not only to continue the study of psychological markers of codependent behavior, but also to search for genetic factors that cause this behavior. Discussion. We have identified the interpretation of the term "codependency" as a phenomenon manifested in dependent behavior caused by a change in value-semantic constructs and a lack of necessary competencies, formed under the influence of negative experience of dysfunctional relationships with significant others. This definition combines a number of approaches and enriches them with a look through the prism of the deep features of a person who exhibits codependent patterns of behavior.